"How did you learn to map?" A model for describing influential learning experiences in geologic mapping. Issue 3 (2nd July 2020) - Petcovic, Heather L.; McNeal, Peggy M.; Nyarko, Samuel Cornelius; Doorlag, Megan H.
Abstract: As much as we think of a geologic map as objective, it is filtered through the experiences of individual geologists and the larger geology community. Thus it is important to understand how geologists become proficient at geologic mapping. As part of a naturalistic study of mapping strategies, 67 geologists ranging from undergraduates to professionals described experiences that promoted personal competence. These interviews were audio-recorded, transcribed, coded and interpreted. Using Lave and Wenger's (1991 ) theory of situated learning, we generated three categories that captured how learning to map is "situated" relative to the instructional, physical, and cultural environments. First, content described how learners acquire skill and knowledge through engaging in practices of experts. Participants reported successfully learning to map through structured progressions that taught content and skill while providing mentored practice. Second, participation captured how learners interact with experiences. Participants described long-term, purposeful immersion in the field during which they learned from experiences that encouraged self-reflection and productive struggle. Finally, community of practice described meaningful relations that allowed learners to become full members of the professional community. Participants reported how working in peer groups, learning from mentors, and teaching others helped them to learn to map. We present a model of how these themes interact in the context of learning to map, and suggest how mapping instruction might leverage influential experiences. Results suggest that the community of practice was a crucial contributor and that learning was defined as much by the professional community as by the physical environment.